SITUATION DETAIL MAPPING OF THE FACULTY OF MATHEMATICS AND NATURAL SCIENCES, UNIVERSITAS NEGERI PADANG USING TOTAL STATION (Georest, 2022)
Detailed Situation Mapping is one of the efforts to provide geospatial information to assist campuses, in this case Padang State University, especially the Faculty of Mathematics and Natural Sciences. Meanwhile Detailed Situation Mapping is a process of measuring and mapping the topography of the earth's surface on a large scale. The situation map contains elements of natural and man-made features on the earth's surface complete with elevation values ​​represented by contour lines. In the measurement process, mapping survey tools are used. One of the tools used is a total station. To make a detailed map of a place, in this case FMIPA UNP, you need location coordinates that are scattered at various points. In order for the resulting maps to be in accordance with geospatial conditions in the field, various applications such as surpac, autocad, arcgis, and so on are used. In the measurement of the horizontal control frame, the closed polygon method was used, while for the measurement of the vertical control frame, the precision flat measurement method was used. For the measurement of detail points, the extrapolation method is used. Meanwhile, for the measurement of high points, the trigonometric method is used using a total station. The type of research used is quantitative research with a descriptive approach. The quantitative research method is a type of research whose specifications are systematic, planned and clearly structured from the start to the creation of the research design. The detail positioning method is carried out for situation mapping at the State University's Faculty of Mathematics and Natural Sciences by measuring the three-dimensional (x, y, z) position of the details determined by the azimuth component (angle, direction and height difference from the tie point). Because of the large amount of detail that is being measured, measurements are made using a fast technique, called tachymetry.